2013
DOI: 10.1111/1567-1364.12045
|View full text |Cite
|
Sign up to set email alerts
|

The involvement of GSH in the activation of human Sod1 linked to FALS in chronologically aged yeast cells

Abstract: Mutations in Cu, Zn-superoxide dismutase (Sod1) have been associated with familial amyotrophic lateral sclerosis, an age-related disease. Because several studies suggest that oxidative stress plays a central role in neurodegeneration, we aimed to investigate the role of the antioxidant glutathione (GSH) in the activation of human A4V Sod1 during chronological aging. Transformation of wild-type and A4V hSod1 into a gsh null mutant and in its parental strain of Saccharomyces cerevisiae indicated that during agin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 52 publications
(78 reference statements)
0
21
0
Order By: Relevance
“…In this case, the co-operation of Mia40 with the MICOS complex was reported to be critical for the efficient targeting of SOD1 in the IMS [103]. Although most studies suggest that CCS1 is critical for the maturation of SOD1, another possibility put forward by Brazil and co-workers is that the glutathione present in the IMS may be critical for the activation of human SOD1 independently of the effect of CCS1 in this process [104,105]. …”
Section: Folding and Assembly Defects In The Ims System Underpin Humamentioning
confidence: 99%
“…In this case, the co-operation of Mia40 with the MICOS complex was reported to be critical for the efficient targeting of SOD1 in the IMS [103]. Although most studies suggest that CCS1 is critical for the maturation of SOD1, another possibility put forward by Brazil and co-workers is that the glutathione present in the IMS may be critical for the activation of human SOD1 independently of the effect of CCS1 in this process [104,105]. …”
Section: Folding and Assembly Defects In The Ims System Underpin Humamentioning
confidence: 99%
“…The import of SOD1 in the IMS relies on the presence of Ccs1 whilst Varabyova et al [59] showed that Mia40 and the MICOS complex regulate the import of the SOD1 mutants that are linked to ALS. Finally, Brazil et al demonstrated that glutathione is essential for the activation of hSOD1 independently of the role of Ccs1 in this process [133], [134].…”
Section: Human Diseasesmentioning
confidence: 99%
“…Other nanocarrier systems for GSH include nanoparticles coated with hydrophilic polymers such as polyethylene glycol or polysaccharides such as chitosan, pectin, hyaluronic acid, and dextran. However, a recent in vitro study by Brasil et al showed that GSH may be involved in the activation of FALS‐linked mutant SOD1 during chronological aging. GSH therefore may not be a suitable therapeutic agent in ALS.…”
Section: Specialized Therapeutic Agent Delivery Systems: a Possible Smentioning
confidence: 99%